2018
DOI: 10.1039/c8ra03145b
|View full text |Cite
|
Sign up to set email alerts
|

Halogen bonding for the design of inhibitors by targeting the S1 pocket of serine proteases

Abstract: Halogen bonding (or X bonding) has attracted increasing interest due to its significant role in molecular recognition in biological systems. Trypsin-like serine proteases have many physiological and pathophysiological functions. There is therefore extensive interest in generating specific inhibitors for pharmacological intervention in their enzymatic activity. We study here if it is possible to use halogenated compounds as the P1 group to bind to the S1 specificity pocket of trypsin-like serine proteases to av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 58 publications
(51 reference statements)
0
7
0
Order By: Relevance
“…In addition, the presence of Br in compound 8p in the p position of the phenyl ring establishes a halogen-π interaction with the Tyr228 residue (3.74 Å) located on one side of the S1 pocket (Figure 4d). The halogen-π interaction has been described for some FXa inhibitors already, such as the anticoagulant rivaroxaban, featuring Cl and Br atoms in their structure [18,43]. The specific alignment of rivaroxaban in the active site allows for the chlorine on the thiophene moiety to interact with the Tyr228 residue in the S1 pocket, mainly through noncovalent halogen-π interactions.…”
Section: Molecular Dockingmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the presence of Br in compound 8p in the p position of the phenyl ring establishes a halogen-π interaction with the Tyr228 residue (3.74 Å) located on one side of the S1 pocket (Figure 4d). The halogen-π interaction has been described for some FXa inhibitors already, such as the anticoagulant rivaroxaban, featuring Cl and Br atoms in their structure [18,43]. The specific alignment of rivaroxaban in the active site allows for the chlorine on the thiophene moiety to interact with the Tyr228 residue in the S1 pocket, mainly through noncovalent halogen-π interactions.…”
Section: Molecular Dockingmentioning
confidence: 99%
“…However, the developed class of compounds was later replaced due to their low bioavailability and inadequate pharmacokinetics [17]. The current strategy uses several types of specific interactions for the design of neutral groups with high affinities to the S1, e.g., halogen bonding, which has been described as essential in FXa inhibitors displaying a halo-aryl group [18][19][20]. For example, the structure of the FXa-rivaroxaban complex revealed a halogen-π interaction between the chlorine of the thiophene group, and the Tyr228 residue located in the lower part of the S1 pocket (Figure 1b, highlighted in blue).…”
Section: Introductionmentioning
confidence: 99%
“…4-Bromobenzylamine 26 is a weak inhibitor of uPA (Ki 1.28 mM), however, its uPA X-ray co-crystal (PDB 5YC6; 1.18 Å) revealed that this simple compound buries deeply into the S1 pocket and forms a non-covalent halogen bond between the electron-withdrawing bromine atom and the electron-rich Asp189. The bromine atom also made two interactions with the backbone carbonyl and side chain hydroxyl of Ser190, and van der Waals interactions were seen between its phenyl group and Ser190, Cys191, Gln192, Trp215, Gly216 and Arg217 (Jiang et al 2018).…”
Section: Non-amidine and Guanidine-based Upa Inhibitorsmentioning
confidence: 99%
“…The crystal structures of HER2 Kinase Domain Complexed with TAK-285 (PDB ID: 3RCD [39]), AKT1 (PDB ID: 4GV1 [40]), ERK2 (PDB ID: 5NHJ [41]), estrogen receptor (PDB ID: 3ERT [42]), uPA (PDB ID: 5YC7 [43]), CDK6 (PDB ID: 1XO2 [44]), and FGF2 (PDB ID: 1FQ9 [45]) were obtained from Protein Data Bank. The 3-dimensional structure of all the studied ligands were built and fully optimized by the HF/6-31(d) level of theory using Gaussian09 program [46].…”
Section: Molecular Docking Simulationmentioning
confidence: 99%